Joint estimation of aboveground biomass using "Space-Air-Ground" data in the Qilian Mountains, China. (May 2022) - Zhang, Zihui; Wu, Shixin; Zhuang, Qingwei; Li, Xiangyi; Zeng, Fanjiang; Xie, Conghui; Hou, Guanyu; Luo, Geping
Highlights: Monitored the spatial heterogeneity and driving mechanism of aboveground biomass (AGB) by combining Space-Air-Ground integrated and Random Forest Regression (RFR) model. Pointed out the main indicators for estimating AGB in different coverage regions. Assessed the applicability of RFR model for estimating the AGB in three different coverage regions. Abstract: Accurate monitoring of aboveground biomass (AGB) and its spatial distribution is essential for sustainable management and development. The most frequently used method for estimating AGB with remotely sensed data is based on the relationship between AGB measured data and vegetation indices. In the past, there were some shortcomings in analyzing the spatial heterogeneity and solving scale difference. Therefore, this paper realized the space-air-ground integrated based on Sentinel-2 Multispectral Instrument (MSI), Unmanned Aerial Vehicle (UAV) and measured data. The results indicated that the RFR models have excellent adaptability to invert AGB of three different coverage regions in study area, with R 2 of 0.69 and root mean square error (RMSE) of 116.22 kg·hm −2 for low-coverage region, R 2 of 0.65 and RMSE of 164.16 kg·hm −2 for medium-coverage region, R 2 of 0.73 and RMSE of 149.99 kg·hm −2 for high-coverage region. We found that the main driving vegetation indices was different in each region during the process of model building and it was related to the characteristics of vegetation indices. Moreover, regions with different coverage have different responses to topography. The findings showed that the spatial distribution and driving mechanism of AGB in the study area could be more clearly analyzed based on the coverage division. The introduction of coverage division reasonably enhanced the accuracy of RFR modeling AGB. This study confirmed that using the Sentinel-2 MSI, UAV images, measured data and the RFR model to realize the space-air-ground integrated is an applicable method for monitoring and assessment of AGB in Qilian Mountains, which can offer scientific basis and theoretical support to rational development of land resources and maintaining the balance of ecosystem.